Perspektif Fraud Diamond dalam Mendeteksi Kemungkinan Kecurangan Laporan Keuangan - Putri, Nur Septiani; Januarti, Indira (E-Jurnal Akuntansi, 2023)
The reliability of BUMN financial reports is not only observed by internal ministries, but the public also supervises them. The research objective is to obtain empirical evidence of the relationship between financial stability, ineffective supervision, rationalization, and the capability function of the board of directors to the possibility of fraudulent financial reporting. The research sample is a BUMN company on the Indonesia Stock Exchange (IDX) which is determined by purposive sampling technique. Data analysis technique using logistic regression. The results of the study show that financial stability, ineffective supervision, rationalization, and the capability of the directors do not affect the possibility of fraudulent financial reporting. The implications of this research for stakeholders and subsequent research are to obtain information about the possibility of fraud in the financial statements of BUMN companies. Keywords: Fraud Diamond; Financial Statement Fraud; State-Owned Company